The impact of IFRS in the financial information of the portuguese companies - Couto, Gualter (2011)
With the purpose of increasing the efficiency of the European finance market, the European Union forced the classified companies in the share market to publish, from January 1st, 2005 onwards, their consolidated financial statements with the support of the International Financial Reporting Standards (IFRS), emanated of International Accounting Standards Board (IASB). This study intends to measure the impact caused by IFRS application in the financial information of the Portuguese business companies, belonging to the Eurolist by Euronext Lisbon. The results demonstrated that the structure of the consolidated balance sheet and income statement suffered a relevant accounting conversion, conditioning the measure made to the performance and the financial position of the business companies. However, one verified that the accounting variations occurred didn't reveal a pattern, being excessively inconstant. The existence of dependent relationships was verified among the relative percentage verified in some accounting items and the business dimension of the companies. The larger the dimension of the studied companies the bigger the impact of the IFRS application.